Potential of ‘long-COVID’ in triggering chronic co-pathologies - Eroğlu, İmdat (Henry Stewart Talks, 2021)
Mounting evidence implicating ‘long-COVID’ as a trigger for chronic pathologies, Range of long-term pathologies already linked to long-COVID, SARS-CoV-2-induced interference of gut physiology and tryptophan biochemistry leading to widespread inflammation across multiple organs, Cellular mechanisms implicated in triggering co-pathologies: SARS-CoV-2 impact on the gut-brain axis, Possible preventive efforts for long-COVID-induced chronic pathologies, and symptoms management and treatments.